On a correlation between EPR data for SASeD doped with Cr³⁺ and soft modes - Lipinski, I.E.; Kuriata, J.; Korynevskii, N.A. (Condensed Matter Physics, 2007)
EPR experimental results obtained for SASeD doped with Cr³⁺ are reported with special emphasis on
those observations which reveal the effect of soft modes i.e. the temperature dependence of the DZZ spin-
Hamiltonian parameter and the temperature dependence of the EPR linewidth. An extension of the twosublattice
model, previously developed and tested for SASD, to include lattice vibrations is presented. The
obtained spectrum of bound excitations for the system investigated supports the idea that soft modes contribute
to the phase transition at TC = 175 K. The anomaly detected at T1 = 150 K has only a quasisoft mode
character and the anomaly detected at T2 = 280 K cannot be related to the effect of soft modes. Експериментальнi результати дослiджень SASeD легованого Cr³⁺ методами ЕПР поданi з наголосом на виявлений вплив м’яких мод, а саме температурної залежностi спiн-гамiльтонового параметра DZZ i ширини лiнiї ЕПР. Двопiдграткову модель, яка була запропонована i апробована раніше для SASD, узагальнено в напрямку врахування коливань гратки. Отриманий спектр зв’язаних коливань системи пiдтверджує iдею про вклад м’яких мод у фазовий перехiд при Tc = 175 K. Аномалiя, виявлена при T1 = 150 K має характер квазiм’якої моди, а аномалiю при T2 = 280 K не можна вiднести до ефекту м’яких мод.